1999
DOI: 10.1074/jbc.274.24.17042
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial Cell Apoptosis Induced by the Peroxisome Proliferator-activated Receptor (PPAR) Ligand 15-Deoxy-Δ12,14-prostaglandin J2

Abstract: 15-Deoxy-⌬12,14 -prostaglandin J 2 (15d-PGJ 2 ) is a bioactive prostanoid produced by dehydration and isomerization of PGD 2 , a cyclooxygenase product. It was recently shown to activate the nuclear peroxisome proliferatoractivated receptor ␥ (PPAR␥), a critical transcription factor involved in adipocyte and monocyte differentiation. In this report, we show that 15d-PGJ 2 is a potent inducer of caspase-mediated endothelial cell apoptosis. PPAR␣, -␦, and -␥ were expressed by endothelial cells, which, when treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

21
298
6
2

Year Published

1999
1999
2007
2007

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 414 publications
(327 citation statements)
references
References 33 publications
21
298
6
2
Order By: Relevance
“…15d-PGJ 2 also inhibited cytokine-induced GM-CSF and G-CSF release; however, in this case, 15d-PGJ 2 did so in a concentration-dependent manner and with equal potency for both survival factors. The effective concentrations used are similar to that required for functional responses in other cells types such as human lung cancer cells (42), epithelial cells (20), endothelial cells (22), and vascular smooth muscle cells (23). The inhibitory effect of 15d-PGJ 2 and ciglitazone on survival factor release is seen at concentrations that also inhibit serum-induced growth.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…15d-PGJ 2 also inhibited cytokine-induced GM-CSF and G-CSF release; however, in this case, 15d-PGJ 2 did so in a concentration-dependent manner and with equal potency for both survival factors. The effective concentrations used are similar to that required for functional responses in other cells types such as human lung cancer cells (42), epithelial cells (20), endothelial cells (22), and vascular smooth muscle cells (23). The inhibitory effect of 15d-PGJ 2 and ciglitazone on survival factor release is seen at concentrations that also inhibit serum-induced growth.…”
Section: Discussionmentioning
confidence: 93%
“…PPAR␥ ligands have been shown to inhibit the release of proinflammatory cytokines from activated macrophages (19) and airway epithelial cells (20). Furthermore, PPAR␥ ligands have been shown to inhibit vascular smooth muscle cell proliferation (21) and induce apoptosis in endothelial cells (22), vascular smooth muscle cells (23), T lymphocytes (24,25), and macrophages (26). However, the potential anti-inflammatory properties of PPAR ligands on airway smooth muscle have not been investigated.…”
mentioning
confidence: 99%
“…PPARg activators may inhibit COX-2 expression, possibly through negative interference with NF-kB and/or AP-1 activation (Inoue et al, 2000;Subbaramaiah et al, 2001;Yang and Frucht, 2001). There is also evidence that supports the function of PPARg ligands as potent inhibitors of angiogenesis in vivo and in vitro, providing an additional mechanism that may partially account for the anticancer properties of PPARg (Bishop-Bailey and Hla, 1999;Xin et al, 1999). Finally, cross-talk between PPARg and other signalling molecules, such as NF-kB, AP-1 and STAT (Ricote et al, 1998;Zhou and Waxman, 1999a,b), may contribute significantly to the effects of PPARg on tumour growth.…”
Section: Discussionmentioning
confidence: 99%
“…Inoue et al demonstrated that 15deoxy-PGJ 2 could reduce PGE 2 production by monocytes in a PPAR␥-dependent manner (31). Moreover, 15deoxy-PGJ 2 and synthetic PPAR␥ ligands are capable of inducing cellular apoptosis of monocytes and endothelial cells and of inhibiting IL-1␤-induced production of NO and matrix metalloproteinase in human chondrocytes through PPAR␥-dependent pathways (32)(33)(34). Overall, both naturally occurring and synthetic ligands for PPAR␥ exert considerable influences on inflammatory responses through receptor-dependent and -independent pathways.…”
Section: Discussionmentioning
confidence: 99%